The Teacher Spiritual Development in the Reference to the Metaphorical Understanding of “Education as a Spiritual Journey” by Parker J. Palmer - Szymańska, Maria (Multidisciplinary Journal of School Education, 2024)
Objective of the article: The aim of the article is to elicit and show the correlation between a spiritual teacher’s development and education seen as a spiritual journey in a pedagogical, personalistic perspective. The research question is as follows: How does the relationship between the teacher’s spiritual development and Palmer’s perception of education in spiritual perception look? Research method: To answer the research question, the method of hermeneutic content analysis seems to be appropriate, as it provides a deeper meaning of education rooted in spirituality for the teacher seen as a unity achieved in the integrative process of formation. A short description of the context of the presented issue: The contents of the article are rooted in the personalistic perspective and cover the reference to spirituality, to some extent corresponding with human spiritual development and teacher spiritual development, tightly connected with Parker J. Palmer’s concept of education perceived in the spiritual dimension. Research findings: The article elicits the meaning of spirituality in the quality of teacher development and the need to provide a space for spirituality in education, in the care of future generations. The research emphasizes that students achieving a spiritual identity on a transpersonal level can become fruitful for contemporary civilization, and further research in this light demands engagement of the broader scientific community, working in the personalistic paradigm. Conclusions and recommendations: Education lacking the space for spirituality determined by higher values does not foster the building of the wholeness of a person and can cause many problems with forming one’s identity, the core of which is a spiritual identity on the autonomous, transpersonal level. The conclusion is that the more “technical/pragmatic” approaches to education are propagated, the more problems in the functioning of future generations can appear. That is why the core curriculum in education needs changing, which should be followed by changes in teacher higher education and training.